The struggle of farming systems in Europe: Looking for explanations through the lens of resilience - Miranda P.M. Meuwissen; Peter H. Feindt; Peter Midmore; Erwin Wauters; Robert Finger; Franziska Appel; Alisa Spiegel; Erik Mathijs; Katrien J.A.M. Termeer; Alfons Balmann; Yann de Mey; Pytrik Reidsma (EuroChoices, 2020)
Many farming systems in Europe are struggling to respond to accumulating economic, environmental, institutional and social challenges. From a resilience perspective, they need three distinct capacities to continue delivering products, income and public goods: robustness, adaptability and transformability. Based on a structured assessment of the resilience capacities of 11 farming systems across Europe we conclude that three mismatches likely contribute to their struggles. First, while farming systems comprised many non-farm actors, resilience strategies largely focused on farms and their robustness, neglecting other options and opportunities. Second, while the delivery of public goods such as biodiversity and attractive landscapes was seen as a major concern, most resilience strategies focused on the delivery of private goods. Third, while in many farming systems actors expressed the need for transformation, farming systems' capacity to transform was perceived as low. Building on the differentiated concept of resilience, findings can guide policymakers, farming system actors, consumers and societal interest groups to identify pathways towards more resilient agricultural systems in Europe.
Keywords: 330